(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article analyzes the theoretical and practical significance of classifying lexical units according to gender characteristics from a sociolinguistic perspective. The study argues that gender is a socio-cultural phenomenon that is manifested not as a linguistic category, but through linguistic units. In particular, the frequency of use, semantic orientation, and pragmatic functions of abstract nouns in the speech of women and men in Uzbek digital discourse are analyzed comparatively. The results show the predominance of abstract nouns related to emotional-expressive and social relations in women’s speech, and the greater use of rational, goal-oriented lexical units in men’s speech. The results of the article serve as an important theoretical and practical basis for language teaching, the creation of gender-appropriate linguodidactic materials, and the improvement of language policy.